Genome-Wide Gene Expression Analysis of Mtb-Infected DC Highlights the Rapamycin-Driven Modulation of Regulatory Cytokines via the mTOR/GSK-3β Axis - Etna, Marilena P.; Severa, Martina; Licursi, Valerio; Pardini, Manuela; Cruciani, Melania; Rizzo, Fabiana; Giacomini, Elena; Macchia, Gianfranco; Palumbo, Orazio; Stallone, Raffaella; Carella, Massimo; Livingstone, Mark; et al. (Frontiers in Immunology, 2021)
In human primary dendritic cells (DC) rapamycin - an autophagy inducer and protein synthesis inhibitor - overcomes the autophagy block induced by Mycobacterium tuberculosis (Mtb) and promotes a Th1 response via IL-12 secretion. Here, the immunostimulatory activity of rapamycin in Mtb-infected DC was further investigated by analyzing both transcriptome and translatome gene profiles. Hundreds of differentially expressed genes (DEGs) were identified by both transcriptome and translatome analyses of Mtb-infected DC and some of these genes were found further modulated by rapamycin. The majority of transcriptome-associated DEGs overlapped with those present in the translatome, suggesting that transcriptionally stimulated mRNAs are also actively translated. In silico analysis of DEGs revealed significant changes in intracellular cascades related to cytokine production, cytokine-induced signaling and immune response to pathogens. In particular, rapamycin treatment of Mtb-infected DC caused an enrichment of IFN-, IFN-and IFN-stimulated gene transcripts in the polysome-associated RNA fraction. In addition, rapamycin led to an increase of IL-12, IL-23, IL-1, IL-6, and TNF- but to a reduction of IL-10. Interestingly, upon silencing or pharmacological inhibition of GSK-3, the rapamycin-driven modulation of the pro- and anti-inflammatory cytokine balance was lost, indicating that, in Mtb-infected DC, GSK-3 functions as molecular switch for the regulation of the cytokine milieu. In conclusion, our study sheds light on the molecular mechanism by which autophagy induction contributes to DC activation during Mtb infection and points to rapamycin and GSK-3 modulators as promising compounds for host-directed therapy in the control of Mtb infection.